Long‐term outcomes of high‐dose‐rate brachytherapy for intermediate‐ and high‐risk prostate cancer with a median follow‐up of 10 years. (7th October 2016) - Yaxley, John W.; Lah, Kevin; Yaxley, Julian P.; Gardiner, Robert A.; Samaratunga, Hema; MacKean, James
Abstract : Objective: To evaluate the long‐term outcomes of high‐dose‐rate (HDR) brachytherapy for patients with intermediate‐ and high‐risk prostate cancer. Subjects and Methods: We retrospectively analysed a prospective longitudinal cohort database including a single‐surgeon series of 507 consecutive men treated with external beam radiotherapy and an HDR prostate brachytherapy boost between August 2000 and December 2009. The risk factors used were based on the D'Amico classification. We measured the incidence of no biochemical evidence of disease (bNED) based on the Phoenix definition of failure (nadir PSA + 2 ng/mL). We also reviewed the incidence of urethral stricture in this cohort. Results: With minimum and median follow‐ups of 6 and 10.3 years, respectively, the bNED rates for men with intermediate‐ and high risk disease were 93.3% and 74.2%, respectively, at 5 years and 86.9% and 56.1%, respectively, at 10 years. The 10‐year bNED rate for men with only one intermediate‐risk factor was 94%, whereas for patients with all three high‐risk factors it was 39.5%. The overall urethral stricture rate was 13.6%. Before 2005, the urethral stricture rate was 28.9% and after January 2005 it was 4.2%. For the 271 men with a minimum follow‐up of 10 years the actuarial 10‐year prostate cancer‐specific survival rate was 90.8% and the actuarial overall survival rate was 86.7%. Conclusions: For men with intermediate‐ or high‐risk prostate cancer features, who are considered not suitable for, or wish to avoid a radical prostatectomy, HDR prostate brachytherapy remains an appropriate treatment option. From December 2004, prevention strategies decreased the risk of post‐brachytherapy urethral strictures.